Effects of Different No-Till Seeders and Tractor Forward Speeds on the Soil Physical Properties and Seed Emergence of Summer Vetch and Winter Wheat - Ahmet Çelik; Sefa Altıkat (Journal of Agricultural Sciences)
The aim of this study is to determine the effects of different no-till seeders and tractor forward speeds on some of soil physical properties and seed emergence of summer vetch and winter wheat. In the research, three different types no-till seeders with hoe (NS-1), single disc (NS-2) and winged hoe (NS-3) type openers were used with four different tractor forward speeds (0.75 m s-1, 1.25 m s-1,1.75 m s-1 and 2.25 m s-1). According to obtained results, the no-till seeders with hoe type furrow opener (NS-1) provided better soil physical properties than the other two no-till seeders. However, tractor forward speeds had no effect on physical properties of soil for both summer vetch and winter wheat. No-till seeders had a significant effect on the mean emergence time (MET) and percentage of emergence (PE) while tractor forward speeds had no effect on these values in both summer vetch and winter wheat. The highest PE was observed at the plots sown with NS-1 seeder in both summer vetch and winter wheat.